2002
DOI: 10.1006/dbio.2002.0823
|View full text |Cite
|
Sign up to set email alerts
|

A Signaling Role for the Uncleaved Form of α6 Integrin in Differentiating Lens Fiber Cells

Abstract: Many alpha integrin subunits are cleaved during their processing to yield heavy and light chains, which remain associated by disulfide bonds. While uncleaved alpha integrin subunits can form functional receptors that sometimes have distinct signaling roles from their better-characterized endoproteolytically cleaved counterparts, their expression at the cell surface and their association with signaling complexes have yet to be determined in vivo. In this study, we demonstrate that, in differentiating lens fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…14,15,23 Uncleaved ␣-subunits might have signaling competence, because they are expressed on the cell surface, maintain their RGD-binding properties, 14,15 and coimmunoprecipitate with the integrin-signaling adapter molecules Shr/Gbr2. 28 A central role in mediating integrin signaling is played by the autophosphorylation of FAK at tyrosine 397 on ECM adhesion, which promotes cell motility. 29 It has been shown that adhesion-dependent FAK phosphorylation requires ␣ v cleavage by PCs.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,23 Uncleaved ␣-subunits might have signaling competence, because they are expressed on the cell surface, maintain their RGD-binding properties, 14,15 and coimmunoprecipitate with the integrin-signaling adapter molecules Shr/Gbr2. 28 A central role in mediating integrin signaling is played by the autophosphorylation of FAK at tyrosine 397 on ECM adhesion, which promotes cell motility. 29 It has been shown that adhesion-dependent FAK phosphorylation requires ␣ v cleavage by PCs.…”
Section: Discussionmentioning
confidence: 99%
“…the closely related ␣3␤1 or ␣7␤1 integrins) are upregulated in the absence of Itga6 expression (see Hynes, 1996). ␣6␤1-laminin interactions have been shown to promote differentiation in some cell types, including skeletal muscle (Sastry et al, 1996) and lens (Walker and Menko, 1999;Walker et al, 2002). However, in these two situations, the differentiation-promoting effect was attributed to the presence of the ␣6A variant.…”
Section: Research Articlementioning
confidence: 99%
“…abundant as lens epithelial cells differentiate into lens fibers (Walker et al, 2002a). Although this form is not endoproteolytically processed, it is expressed at the cell surface and associates with signaling molecules such as Shc and Grb2 (Walker et al, 2002a).…”
Section: A D B E C Fmentioning
confidence: 99%
“…Although this form is not endoproteolytically processed, it is expressed at the cell surface and associates with signaling molecules such as Shc and Grb2 (Walker et al, 2002a).…”
Section: A D B E C Fmentioning
confidence: 99%